2010
DOI: 10.1016/j.jmb.2010.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Conserved Retroviral RNA Packaging Element by NMR Spectroscopy and Cryo-Electron Tomography

Abstract: The 5′-untranslated regions (5′-UTRs) of all gammaretroviruses contain a conserved “double hairpin motif” (ΨCD) that is required for genome packaging. Both hairpins (SL-C and SL-D) contain GACG tetraloops that, in isolated RNAs, are capable of forming “kissing” interactions stabilized by two intermolecular G-C base pairs. We have determined the three-dimensional structure of the double hairpin from the Moloney Murine Leukemia Virus (MoMuLV) ([ΨCD]2, 132-nucleotides, 42.8 kDaltons) using a 2H-edited NMR spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 119 publications
5
73
0
Order By: Relevance
“…Instead, when Gag expression was constant and gRNA expression in cells increased, the amount of gRNA per particle increased proportionately until an upper limit was reached, beyond which a 10-fold further increase in vector expression neither increased the amount packaged per virion nor decreased the level of virus production. These observations of saturable gRNA packaging and no impairment of virion release in the presence of excess gRNA support the hypothesis that recruitment of the conserved copy number of gRNAs per MoMLV particle-presumably a single dimer-triggers an assembly transition that prevents the inclusion of excess gRNA (53,54).…”
Section: Discussionsupporting
confidence: 71%
“…Instead, when Gag expression was constant and gRNA expression in cells increased, the amount of gRNA per particle increased proportionately until an upper limit was reached, beyond which a 10-fold further increase in vector expression neither increased the amount packaged per virion nor decreased the level of virus production. These observations of saturable gRNA packaging and no impairment of virion release in the presence of excess gRNA support the hypothesis that recruitment of the conserved copy number of gRNAs per MoMLV particle-presumably a single dimer-triggers an assembly transition that prevents the inclusion of excess gRNA (53,54).…”
Section: Discussionsupporting
confidence: 71%
“…Experiments on selectively labeled J236 RNAs were particularly valuable for analysis of NMR data given that J236 is larger than 60 nt. In fact, only a few NMR structures are available for such larger RNAs (Lukavsky et al 2003;D'Souza et al 2004;Miyazaki et al 2010;Burke et al 2012;Miller et al 2014;Keane et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Studies of MLV packaging showed that the monomeric and dimeric RNAs have very different secondary structures (10,15,21). Furthermore, dimerization of MLV RNAs exposes highaffinity binding sites for nucleocapsids, which is critical for RNA packaging (16,22). It is thought that exposure of these sites allows Gag binding, leading to the incorporation of RNA into virus particles.…”
Section: Discussionmentioning
confidence: 99%